Analysis of Vaginal Microbiome in Women with or Without Episodes of Spontaneous Abortion in Eastern Nigeria - Felix Emele Emele; Prisca Onyeulor; Francisca Nwaokorie; Damian Asogwa (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: Spontaneous abortion (miscarriage) is a common adverse pregnancy outcome earth-wide, and has remained a challenge in Nigeria. This study aimed at comparing the vaginal microbiome of women who have had episodes of spontaneous abortion with those who have not experienced any incident - in order to find out any possible role of vaginal microbiota in spontaneous abortion.